LEGAL PROTECTION AGAINST CONTINUOUS MONEY LAUNDERING IN THE TAX SECTOR IN INDONESIA - Ulfah Nurfadilah; Iwan Darmawan (Awang Long Law Review, 2026)
Legal protection against money laundering crimes occurring in the context of taxation in Indonesia. Money laundering involving the tax sector is a serious issue that can disrupt economic stability and national revenue. This study explains the legal framework governing efforts to prevent and combat money laundering, particularly those related to taxation practices, and also identifies weaknesses and challenges in its implementation. The definition of tax crimes includes tax evasion thru forgery committed by individuals or by people working within a legal entity, usually involving collaboration between taxpayers and tax officials for personal gain. Criminal policies related to money laundering in handling tax crimes demonstrate a strong connection between source crimes, such as crimes in the tax sector considered predicate crimes, and money laundering offenses, which can be seen as their derivative. The obstacles and challenges in resolving tax crimes thru the anti-money laundering system are related to weaknesses in the existing evidence system in Indonesian criminal law.